Automatic Gas Leakage Detection using IOT. Issue 4 (December 2020) - Dwibedi, Rajat Kumar; Vanitha, V.; Sagar, R D; PhaniSai, P; GanjikuntaYeshwanth,
Abstract: The gas detectors can be used for the detection of combustible, flammable and poisonous gases and for loss of oxygen, and also to detected a gas leak or other pollutants. It makes the area where the leak occurs an warning sound and instructs operators to leave the area. The system proposed is planned, built and sent an SMS warning system for detection of gas leakages. Infrared imaging sensors have recently been used for a number of applications in industrial plants and refineries.